2016
DOI: 10.1016/j.chiabu.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and behaviors of dentists regarding child physical abuse in Jeddah, Saudi Arabia

Abstract: A large proportion of child physical abuse cases go undocumented and unreported. Dentists can play an important role in identifying and reporting these cases, but little has been reported about this issue in Saudi Arabia. The aims of the study were to (1) assess dentists' knowledge of child physical abuse, (2) assess dentists' attitudes towards child physical abuse, and (3) assess the behaviors of dentists in identifying and reporting child physical abuse. A cross-sectional survey of pediatric dentists, pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
74
2
11

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(94 citation statements)
references
References 9 publications
7
74
2
11
Order By: Relevance
“…The response rate has decreased slightly from 2008 to 2013, but was as high as or higher than response rates from similar studies in other countries [6,[16][17][18]. Among colleagues the notion of fatigue of participating in questionnaire studies are discussed.…”
Section: Discussionmentioning
confidence: 97%
“…The response rate has decreased slightly from 2008 to 2013, but was as high as or higher than response rates from similar studies in other countries [6,[16][17][18]. Among colleagues the notion of fatigue of participating in questionnaire studies are discussed.…”
Section: Discussionmentioning
confidence: 97%
“…This disparity is in accordance with other studies. [22][23][24][25][26][27][28][29][30][31] The challenges dental health personnel experience when suspecting child maltreatment and deciding whether to report to CWS may be related to difficulties making decisions under uncertainty. [32] More specifically, signs of child maltreatment are often unclear and ambiguous and the consequences of reporting to CWS are often unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[21] International studies have shown that dental health personnel do suspect child maltreatment among their patients. [22][23][24][25][26][27][28][29][30] However, detecting child maltreatment can be difficult, and in relation to oral health, it is hard to determine common features that characterize dental neglect. [18] Dental health personnel find their duty to report challenging and do often fail to report their suspicions to CWS.…”
Section: Introductionmentioning
confidence: 99%
“…In countries like Germany and Pakistan, the professionals do not have the obligation to notify suspected or confirmed cases of violence against children and adolescents to competent bodies; in Saudi Arabia, the notification has only become required from education and health professionals since 2009 (10,(15)(16) . In Brazil, the protection of children and adolescent victims of interfamily violence is ensured by the Federal Constitution of 1988 and the Statute of the Children and Adolescents (ECA) which was established in 1990, and puts the country in a prominent position for being considered as having one of the most advanced laws in the defense of child and adolescent rights.…”
Section: Discussionmentioning
confidence: 99%